2018
DOI: 10.1210/en.2017-03253
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Insulin-like Androgenic Gland Hormone Receptor Gene Specifically Expressed in Male Chinese Shrimp

Abstract: The insulin-like androgenic gland hormone (IAG) is the key regulator in crustacean male sexual differentiation. As a secreted peptide hormone, IAG might perform its biological function through interacting with the membrane receptor. However, the receptor of IAG remains unclear. In the current study, a putative IAG receptor gene (FcIAGR) was identified in Fenneropenaeus chinensis. The deduced amino acid sequence of FcIAGR contained several conserved domains of insulin-like receptor proteins, including two L dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…As the functional core of the axis, AG controls male sexual differentiation through secreting the sexual hormone IAG (Ventura and Sagi, 2012). We previously identified a male specific expressed IAG receptor, FcIAGR, from the shrimp F. chinensis (Guo et al, 2018). Knockdown of FcIAGR expression in a late developmental stage of shrimp retarded testis development, which provided evidence to the downstream of the "eyestalk-AG-testis" endocrine axis.…”
Section: Discussionmentioning
confidence: 98%
“…As the functional core of the axis, AG controls male sexual differentiation through secreting the sexual hormone IAG (Ventura and Sagi, 2012). We previously identified a male specific expressed IAG receptor, FcIAGR, from the shrimp F. chinensis (Guo et al, 2018). Knockdown of FcIAGR expression in a late developmental stage of shrimp retarded testis development, which provided evidence to the downstream of the "eyestalk-AG-testis" endocrine axis.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the studies have shown the existence of transcripts for putative peptide hormones in the ovary: the red swamp crayfish Procambarus clarkii (47), the Australian red-craw crayfish Cherax quadricarinatus (49), and the giant freshwater prawn Macrobrachium rosenbergii (51). In addition to the peptide/protein hormone candidates, the transcriptomic data have been exploited for the identification and characterization of peptide hormone receptors (53,54) and the elucidation of molecular pathways involved in the regulation of various biological functions (55,56). Hence, transcriptomics is an essential tool in the quest to improve our understanding of reproductive biology underlying peptide hormones and their receptors in peripheral organs such as the gonads.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in the penaeid Fenneropenaeus the RTK4 ortholog is exclusively expressed in the testis (Guo et al, 2018). In the SRAs analyzed here reads for RTK4 orthologs are found mostly, but not exclusively in the testes and androgenic glands.…”
Section: Expressionmentioning
confidence: 66%
“…Of course, it also remains possible that one or more of these RTKs use neither of these peptides, but yet another ligand. Within this context it is interesting that orthologs of what has been labeled RTK4 here have been shown to interact with androgenin in two different species (Aizen et al, 2016;Guo et al, 2018). In Fenneropenaeus chinensis RTK4 is exclusively expressed in males and the expression data analyzed here for the closely related P.…”
Section: Page 11mentioning
confidence: 81%
See 1 more Smart Citation